Evolution and Phylogeography of the Nonpathogenic Calicivirus RCV-A1 in Wild Rabbits in Australia - Jahnke, Marlene (American Society for Microbiology (ASM), 2010)
Despite its potential importance for the biological control of European rabbits, relatively little is known about the evolution and molecular epidemiology of rabbit calicivirus Australia 1 (RCV-A1). To address this issue we undertook an extensive evolutionary analysis of 36 RCV-A1 samples collected from wild rabbit populations in southeast Australia between 2007 and 2009. Based on phylogenetic analysis of the entire capsid sequence, six clades of RCV-A1 were defined, each exhibiting strong population subdivision. Strikingly, our estimates of the time to the most recent common ancestor of RCV-A1 coincide with the introduction of rabbits to Australia in the mid-19th century. Subsequent divergence events visible in the RCV-A1 phylogenies likely reflect key moments in the history of the European rabbit in Australia, most notably the bottlenecks in rabbit populations induced by the two viral biocontrol agents used on the Australian continent, myxoma virus and rabbit hemorrhagic disease virus (RHDV). RCV-A1 strains therefore exhibit strong phylogeographic separation and may constitute a useful tool to study recent host population dynamics and migration patterns, which in turn could be used to monitor rabbit control in Australia.